Permanent Magnet Axial Length Optimization for Transverse Magnetic Flux Generator with Disk Rotor - Duniev O.; Yehorov A.; Masliennikov A.; Stamann M.; Dobzhanskyi O. (Problems of the Regional Energetics, 2021)
Based on the analysis of the transverse flux machine designs, they were found to have a relative design simplicity and a high-power density. The purpose of this work is to determine the optimal height of a permanent magnet and to define its effect on the induced EMF value in the stator coils and the cogging torque, as well as to define the picture of the magnetic flux leakage between the stator poles. To achieve these goals, the 3D model of a low speed generator was studied. The electromagnetic analysis was carried out using a modern software, which allows us to determine the magnetic field distribution in the 3D, as well as the induced EMF value and the rotor cogging torque. The criterion for the optimal calculation is the highest EMF value at the minimum value of the rotor cogging torque. The parameters of the permanent magnets, such as the width and length, remained unchanged, whereas, the height varied from 1 to 8 mm at a 1-mm step. The corresponding dependencies are obtained for each height. The most significant result of the work is the conclusion that the height of the permanent magnet should not exceed the 3-mm value. The significance of the obtained results is that the used methodology allowed finding the optimal height of the permanent magnet, since a further increase in its height leads to no growth in the EMF value, but rather significantly enhances the negative effect from the rotor cogging torque. In addition, the simulation results were supported experimentally.